2020
DOI: 10.1128/ecosalplus.esp-0003-2020
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Residency in the Gut of Healthy Human Adults

Abstract: Escherichia coli is one of the most well-studied bacterial species, but several significant knowledge gaps remain regarding its ecology and natural history. Specifically, the most important factors influencing its life as a member of the healthy human gut microbiome are either underevaluated or currently unknown. Distinct E. coli population dynamics have been observed over the past century from a handful of temporal studies conducted in healthy human adults. Early studies using serology up to the most recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 124 publications
(172 reference statements)
0
77
0
3
Order By: Relevance
“…Escherichia coli, widely exists in the intestinal tract of humans and animals. When the intestinal ora is dysregulated or the body's immune system is disturbed, Escherichia coli will become pathogenic bacteria and cause intestinal diseases or other diseases of organizational organs (Martinson et al 2020). After the intervention of Probio-M9, The contents of E. faecalis and E. Coil are decreased signi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli, widely exists in the intestinal tract of humans and animals. When the intestinal ora is dysregulated or the body's immune system is disturbed, Escherichia coli will become pathogenic bacteria and cause intestinal diseases or other diseases of organizational organs (Martinson et al 2020). After the intervention of Probio-M9, The contents of E. faecalis and E. Coil are decreased signi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…It is harmless to humans and animals and has good biocompatibility. It competes with harmful bacteria that adhere to the intestines to reduce the risk of harmful bacteria reproduction, maintain the stability of the intestinal ora, balance the composition of the intestinal ora; Lactobacillus reuteri also has the effect of improving allergies and enhancing human immunity (Martinson et al 2020). Studies have shown that Lactobacillus reuteri produces lactic acid, acetic acid and other substances after glycolysis and pentose phosphate metabolism.…”
Section: Path Analysismentioning
confidence: 99%
“…In humans, E. coli is present at less than 1% of gut microbiota and it is not among the 25 most prevalent bacteria [1,2]. But E. coli is the predominant Enterobacteriaceae species in humans [3]. Interestingly, E. coli is the first to colonize the intestines and persists all through life in humans [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some E. coli strains known as pathobionts do not cause any disease in healthy individuals but exacerbate chronic inflammatory diseases [1]. The E. coli population in the GI tract is dynamic with a turnover in months to years [3,6]. Humans contain five different strains of E. coli [7].…”
Section: Introductionmentioning
confidence: 99%